Putative Second-Site Mutations in the Barley Low Phytic Acid 1-1 (lpa 1-1) Genetic Background Further Reduce Seed Total Phosphorus - Beverly L. Agesa; Victor Raboy; Paul J. A. Withers; Katherine A. Steele (Agronomy)
Inefficient crop phosphorus (P) use impacts global food security and P fertilizer use can be environmentally harmful. Lines homozygous for barley (Hordeum vulgare L.) low phytic acid 1-1 (lpa 1-1) have yields equivalent to the wild type but ~15% less seed Total P (TP). The objective here was to identify second-site mutations in the lpa1-1 background that condition a further reduction in seed TP, again with little impact on yield. A chemically mutagenized population was derived from lpa 1-1 and screened to identify lines with seed TP reductions greater than 15% (as compared with wild-type) but with seed weights per plant within 80% of wild-type. Three M4 lines were selected and evaluated in a greenhouse pot experiment. Plants were grown to maturity either on a soil with low soil P fertility (16 to 25 mg Olsen P L−1; Soil P Index 1) or with that soil supplemented (36 kg P ha−1) to provide optimal available soil P. Mean seed P reduction across the three lines and two soil P levels was 28%, a near doubling of the lpa1-1 seed Total P reduction. When grown with optimal soil available P, no impact of these putative mutations on grain yield was observed. These findings suggest that the three lpa 1-1-derived mutant lines carry second-site mutations conferring substantially (~17%) greater decreases in seed TP than that conferred by lpa 1-1. If the putative mutations are confirmed to be heritable and to have negligible impact on yield, they could be used in breeding P-efficient barley cultivars as a step towards reducing regional and global P demand.